Governance mechanisms and disclosure among Malaysian Islamic banks - Marsidi, Asri; Annuar, Hairul Azlan; Abdul Rahman, Abdul Rahim (2016)
Decent corporate governance practices are important and fundamental in today’s corporate world, particularly in the growing and high future prospect of Islamic banking industry. In this respect, its linkages with disclosure at Islamic banks need to be well understood and developed for better sustainability of the industry. This study is hence conducted to examine the impact of corporate governance on the Islamic financial and social reporting (IFSR) of Islamic banks in Malaysia. Drawing on surveys this study seeks the views of accountants working in Islamic banks regarding the importance of items in the IFSR index developed by Marsidi et al. (2016). The annual reports are used to examine the score of the IFSR for the Islamic banks as well as to collect the data for the related variables. The multivariate regression results suggest that board size is a significant factor in explaining the IFSR at Islamic banks in Malaysia. Such finding is perceived as contributing towards the suitable formation of board of directors specifically in terms of the total number of directors at Islamic banks. The study also contributes towards the use of Islamic agency theory in the context of Islamic banks. From another perspective, the findings of the study contribute towards the development and sustainability of Islamic banks both in Malaysia and throughout the globe.